2019
DOI: 10.1038/s41598-019-56378-y
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and interfacial properties of decane in the presence of carbon dioxide, methane, and their mixture

Abstract: Molecular dynamics simulations were performed to study the bulk and interfacial properties of methane + n-decane, carbon dioxide + n-decane, and methane + carbon dioxide + n-decane systems under geological conditions. In addition, theoretical calculations using the predictive Peng-Robinson equation of state and density gradient theory are carried out to compare with the simulation data. A key finding is the preferential dissolution in the decane-rich phase and adsorption at the interface for carbon dioxide fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
112
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(134 citation statements)
references
References 65 publications
22
112
0
Order By: Relevance
“…The total density profiles did not exhibit adsorption at the interfaces, probably due to the long length of the chains. Similar density profiles have been reported in the literature for large linear alkanes [39][40][41]. We observed that the system at the lower T did not develop a central zone characterized by a flat density, which corresponds to the homogeneous bulk liquid.…”
Section: Density Profilessupporting
confidence: 89%
“…The total density profiles did not exhibit adsorption at the interfaces, probably due to the long length of the chains. Similar density profiles have been reported in the literature for large linear alkanes [39][40][41]. We observed that the system at the lower T did not develop a central zone characterized by a flat density, which corresponds to the homogeneous bulk liquid.…”
Section: Density Profilessupporting
confidence: 89%
“…Fig. 1), are usually found to be in good agreement [12,15,17,18,20,23,[78][79][80][81][82][83][84][85][86]. This indicates that the underlying density profiles (including the contribution of the enrichment to Γ 2 , it should be noted that only the latter is thermodynamically rigorously defined, in a sense that it can be derived from thermodynamic potentials (see Appendix), whereas the enrichment was introduced as a simple geometric measure to characterise the surface excess regarding the non-monotonicity of the density profiles.…”
Section: Nanoscopic Interfacial Properties: Enrichment and Relative Adsorptionmentioning
confidence: 75%
“…This interesting phenomenon has been reported since the early days of theoretical studies of interfacial properties of mixtures [7][8][9][10][11][12][13]. Its presence has been confirmed by different independent theoretical methods for many systems [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The enrichment has caused much attention in the past decades, e.g.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Due to the molecular structure effect at the thin liquid film, especially the macro-molecules like polymers existing in the film, attentions on structural forces have been arisen in recent years to explain phenomena including colloid and polymer stability, while the classical DLVO theory fails [63,64]. If hydrated cation adsorption occurs with hydrogen bonding network formed/broken or ion exchange induced, hydration force will appear and be recognized as primary or secondary force respectively [65,66].…”
Section: Double Layer Expansionmentioning
confidence: 99%